Hambatan Penerapan Kurikulum Kulliyatu al-Mu’allimîn al-Islâmiyyah pada Pembelajaran Bahasa Arab di Pondok Pesantren Raudhotus Salâm Yogyakarta - hafiz, muhammad khafid jenur; Lukluk , Rohmatun (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
This research aims to describe the problems of application of the KMI curriculum at the Raudhatus Salaam Islamic Boarding School, Yogyakarta, which includes the problems and implementation of the KMI curriculum. This research uses a descriptive qualitative approach. The data collection methods used were observation, interviews, and documentation. Respondents in this study included the principal, the curriculum department, and one teacher. The research used a process of data reduction, data presentation, and drawing conclusions to analyze the data. The findings show that: The Kulliyatul Mu'allimin Al-Islamiyah curriculum at the Raudhatus Salaam Islamic Boarding School has similarities with the KMI at Pondok Modern Darussalam Gontor. The KMI curriculum at both Islamic boarding schools has a similar structure, with 70% focus on religious knowledge and 30% on general science. The learning process lasts 24 hours and is supervised by the Kyai/President of the Islamic Boarding School, Peduli Santri, Deputy Director of KMI, as well as the Teacher/Ustadz who is responsible for Service and Organization at the Raudhatus Salaam Islamic Boarding School. KMI teachers and staff face difficulties in implementing the KMI curriculum in Arabic language learning because they still follow the Ministry of National Education curriculum and the KMI curriculum.